1987
DOI: 10.1111/j.1365-246x.1987.tb05202.x
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic dispersion of short-period P-waves due to scattering and multipathing

Abstract: The delay of high frequencies in the teleseismic short-period explosion P-wave due to scattering is observed at a number of high Q sites.Recordings for the arrays NORSAR, YKA, GBA, and EKA have been examined as well as the individual sites RSNT, RSON, RSNY, RSSD, ANTO, CTAO, and KONO. P-waves from Eastern Kazakh explosions observed at NORSAR, and several high Q stations show a systematic delay of high frequencies (4-5 Hz) relative to lower frequencies (1 -2 Hz) by as much as 0.5 s. This apparent dispersion is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Examining long propagation-distance P-wave signals from an explosion recorded at the NORSAR array, McLaughlin and Anderson (1987) found that 5 Hz-band signals arrive later than those in the 1 Hz band. Comparison with numerical simulations of P-wave propagation through a random medium, they interpreted the observed velocity dispersion to be caused by randomness having multiple correlation distances.…”
Section: Envelopes Of Teleseismic P-wavesmentioning
confidence: 98%
“…Examining long propagation-distance P-wave signals from an explosion recorded at the NORSAR array, McLaughlin and Anderson (1987) found that 5 Hz-band signals arrive later than those in the 1 Hz band. Comparison with numerical simulations of P-wave propagation through a random medium, they interpreted the observed velocity dispersion to be caused by randomness having multiple correlation distances.…”
Section: Envelopes Of Teleseismic P-wavesmentioning
confidence: 98%
“…(1992). In an earlier publication, McLaughlin and Anderson (1987) showed both theoretically and empirically that scattering preferentially delays high frequencies; McCartor (1991) andFisk et. al.…”
Section: List Of Figuresmentioning
confidence: 99%
“…The finite-difference method has been used by several workers to study the effects of stochastic perturbations to simple velocity models Clayton, 1984, 1986;McLaughlin et al, 1986;McLaughlin and Anderson, 1987;Dougherty and Stephen, 1988;Charette, 1991;Toks6z et al, 1991]. Such studies show that stochastic scattering can appreciably alter the spectral content of the first arrival [Frankel and Clayton, 1986;Charette, 1991].…”
Section: The Effect Of Deterministic Scatteringmentioning
confidence: 99%
“…Stephen [1990] examined acoustic benchmark solutions for a perfect wedge, a lossless penetrable wedge, and a plane-parallel waveguide. Finite-difference studies of complex media have dealt extensively with the scattering from random media Clayton, 1984, 1986;McLaughlin et al, 1986;McLaughlin and Anderson, 1987;Dougherty and Stephen, 1988;Charrette, 1991;Toksdz et al, 1991]. However, such studies have generally been limited to mean velocity perturbations of 5-20%, values significantly smaller than the variations in the magma chamber model (Figure 3.3).…”
mentioning
confidence: 99%